2013
DOI: 10.1073/pnas.1303573110
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to a conserved antigenic target is protective against diverse prokaryotic and eukaryotic pathogens

Abstract: Microbial capsular antigens are effective vaccines but are chemically and immunologically diverse, resulting in a major barrier to their use against multiple pathogens. A β-(1→6)-linked poly-N-acetyl-D-glucosamine (PNAG) surface capsule is synthesized by four proteins encoded in genetic loci designated intercellular adhesion in Staphylococcus aureus or polyglucosamine in selected Gram-negative bacterial pathogens. We report that many microbial pathogens lacking an identifiable intercellular adhesion or polyglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
209
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(214 citation statements)
references
References 57 publications
3
209
1
1
Order By: Relevance
“…To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks. Exopolysaccharides such as PNAG, a major component of bacterial biofilms, are broadly distributed among diverse microbes (27). Using antibodies directed against PNAG as a proxy to gauge biofilms within the tick, P1-injected I. scapularis guts showed a marked reduction of biofilms, similar those with A. phagocytophilum infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks. Exopolysaccharides such as PNAG, a major component of bacterial biofilms, are broadly distributed among diverse microbes (27). Using antibodies directed against PNAG as a proxy to gauge biofilms within the tick, P1-injected I. scapularis guts showed a marked reduction of biofilms, similar those with A. phagocytophilum infection.…”
Section: Discussionmentioning
confidence: 94%
“…PNAG is broadly distributed in diverse microbes and can be detected by a specific antibody (27). Having observed native biofilm formation in tick guts using a PNAG antibody (SI Appendix, Fig.…”
Section: The Peritrophic Matrix Is Essential For Colonization Of the mentioning
confidence: 99%
“…The conserved exopolysaccharide known as polysaccharide intercellular adhesin was originally identified in the biofilms of S. epidermidis (11) and Staphylococcus aureus (12) and has now been shown to be produced by various Gram-negative bacteria (13)(14)(15)(16)(17)(18)(19) and higher eukaryotes (20). Polysaccharide intercellular adhesin is synthesized as a ␤-1,6-linked poly-N-acetyl-Dglucosamine (PNAG) 5 polymer and subsequently modified by partially de-N-acetylation and/or O-succinylation.…”
mentioning
confidence: 99%
“…The greater effect of the post-infection goat antiserum on the ica − strain compared to the ica + strain suggests that the presence of the PNAG antigen on the bacterial surface reduces the efficacy of the antibodies against the non-PNAG antigens on the bacterial surface. PNAG, also known as intercellular adhesion polysaccharide (20), is a surface polymer produced by both S. aureus and S. epidermis, and many other pathogens (21). PNAG promotes biofilm formation and enhances staphylococcal virulence in mouse infection models (12,22).…”
Section: Discussionmentioning
confidence: 99%